Valence Band Offsets of ZnO/SrTiO3, ZnO/BaTiO3, InN/SrTiO3, and InN/BaTiO3 Heterojunctions Measured by X-Ray Photoelectron Spectroscopy - Jia, Caihong; Chen, Yonghai; Liu, Xianglin; Yang, Shaoyan; Wang, Zhanguo (IntechOpen, 2011)
None